Classics of philosophy - Pojman, Louis P. (Oxford, 2003)
Classics of Philosophy, 2/e is the most comprehensive anthology of writings in western philosophy in print. Spanning 2,500 years of thought, it is ideal for introduction to philosophy and history of philosophy courses that are structured chronologically. Over seventy-five works by forty-three philosophers as well as fragments from the Pre-Socratics are included, offering students and general readers alike an extensive and economical collection of the major works of the western tradition. This anthology contains the most important writings from Thales to Rawls; twenty-three of these are complete works, while the others are judiciously abridged so that little of value to the student is lost. The book provides a broad view of the most significant stages of growth in Western philosophy, including its birth with the Pre-Socratics as well as its contemporary developments. A lucid introduction, including a brief biographical sketch, accompanies each of the featured philosophers. The second edition includes new or revised selections by the Pre-Socratics, Aristotle, Augustine, Locke, Berkeley, Hume, Kierkegaard, Wollstonecraft, Nagel, and Foot.